Amplification of mecA gene in multi-drug resistant Staphylococcus aureus strains from hospital personnel - Asad U Khan,1 Ayesha Sultan,1 Anju Tyagi,2 Shazia Zahoor,3 Mohd Akram,1 Sukhminderjit Kaur,3 Mohd Shahid,2 Chetana V Vaishnavi1 (The Journal of Infection in Developing Countries, 2007)
Background: Antibiotic resistance is common among bacterial pathogens associated with both community acquired and nosocomial infections. In view of the present problem of drug resistance we investigated the prevalence of methicillin resistant Staphylococcus aureus (MRSA) and amplified the mecA gene in the isolates from the hand swabs of the hospital personnel.Methodology: The nuc gene was amplified to characterize these isolates at species level. The S. aureus isolates were analyzed for their susceptibility to different classes of antibiotics using the disk diffusion method. The spot inoculation test was performed to detect methicillinase production in these isolates.Results: In the screened isolates of S. aureus, 14.2 and 15 kb of plasmids were present. These isolates showed pronounced resistance against â-lactam antibiotics including second- and third-generation cephalosporins, aminoglycosides, macrolides and fluoroquinolone. Some of the isolates included in this study were resistant to three or more antibiotics. Expression of methicillinase was detected by spot inoculation test, and a few of the isolates were found to produce methicillinase. Moreover, mecA gene was also amplified. Of 17 isolates only 7 showed presence of mecA gene.Conclusion: This study highlights the emerging trend of multiple drug resistance in S. aureus strains isolated from hospital personnel working in a premier hospital in North India.